The hindu world - Bahree, Patricia (Hodder Wayland London, 2001)
Hinduism if the world's oldest living faith. This book explores what it means to be a Hindu. It explains the rites associated with birth, marriage and death; the importance of the family; customs and taboos; holy places and shrines. It also takes us inside a Hindu temple, and describes the festivals of the Hindu calendar.